Cardiovascular Magnetic Resonance Imaging clarifies cardiac pathophysiology in early, asymptomatic diffuse systemic sclerosis - I. Mavrogeni, Sophie; Bratis, Konstantinos; Karabela, Georgia; Spiliotis, George; van Wijk, Kees; Hautemann, David; H.C. Reiber, Johan; Koutsogeorgopoulou, Loukia; Markousis-Mavrogenis, George; Kolovou, Genovefa; Stavropoulos, Efthymios (Inflammation & Allergy-Drug Targets (Discontinued), 2015)
Background: Myopericardial inflammation, perfusion’s defects and fibrosis are major causes of cardiac disease in scleroderma (SSc). We hypothesized that using inflammation and stress perfusion-fibrosis cardiovascular magnetic resonance (CMR), we can identify the pathophysiology of heart disease in asymptomatic diffuse SSc. Patients-Methods: 46 recently diagnosed, asymptomatic patients with diffuse SSc had a CMR examination using a 1.5T system. ECG gated breath hold cine and short tau inversion recovery (STIR) T2 images were initially acquired. If T2 ratio<2 a stress perfusion-fibrosis protocol was applied. If T2>2 a myocarditis protocol including early (EGE) and late (LGE) gadolinium imaging was applied. SSc patients’ results were compared with age and sex-matched controls and patients with coronary artery disease (CAD). Results: In 2/46 SSc with T2 ratio>2, the myocarditis protocol was positive for acute myocardial inflammation, who developed clinical signs of acute myocarditis shortly after the CMR evaluation. In the rest 44/46 with T2 ratio<2 the stress perfusion-fibrosis CMR identified a significant reduction in Myocardial Perfusion Reserve Index (MPRI) compared with matched controls (0.6±0.4 vs 3.2±0.8, p<0.001), but not with CAD (0.6±0.4 vs 0.86±0.46, p=NS) and correlated only with the presence of digital ulcers (p<0.05). The scar was diffused and greater compared to controls, but did not differ from that assessed in CAD. Two years follow up, available in 11/44 SSc, showed further asymptomatic MPRI deterioration in all and diffuse subendocardial LGE in 8/11, without any change in LV, RV volumes and ejection fractions. Conclusion: CMR may reveal severe cardiac involvement in early, asymptomatic diffuse SSc with normal routine cardiac evaluation, presenting either as myocardial inflammation or as severe reduction of MPRI and diffuse fibrosis with further deterioration in the long term follow up.
Keywords: Systemic sclerosis